The deubiquitinase ElaD is present in the majority of Escherichia coli strains - Wang, Xinyu; Guo, Weiqi; Hu, Jiangang; Zhang, Beibei; Qi, Jingjing; Tian, Mingxing; Bao, Yanqing; Deng, Lei; Wang, Shaohui (Frontiers in Microbiology, 2025)
BackgroundPathogens employ a variety of effectors to modulate key host signaling pathways, thereby facilitating bacterial survival and enhancing pathogenicity. Despite lacking a complete ubiquitin system of their own, bacterial effectors frequently function as ubiquitin ligases or deubiquitinases (DUBs) to disrupt the eukaryotic ubiquitin machinery. DUBs have been found in a variety of bacteria, including ElaD, which has recently been recognized as a DUB in Escherichia coli (E. coli). However, the distribution and evolutionary analyses of ElaD in different E. coli remains largely unknown.MethodsWe retrieved and analyzed the elaD gene sequences of 530 E. coli strains. Then, molecular characterization of each strain was determined. According to all the statistical information, the distribution of elaD gene in E. coli was comprehensively investigated, and the relationship between elaD and E. coli pathotypes, serotypes, phylogenetic groups and MLSTs was analyzed. Phylogenetic tree was also constructed to analyze the evolutionary relationships between different ElaD.ResultsOur findings demonstrate that the elaD gene was present in 66.60% (353/530) of both pathogenic and nonpathogenic E. coli strains. elaD gene is predominantly found in the O157, O26, O139 and O8 serotypes. The majority of elaD-positive strains belonged to phylogenetic groups B1, A, E and D, with the predominant sequence types being ST11, ST21, ST10, ST1 and ST69. ElaD from different strains clustered in the phylogenetic tree in a correlation with O serotypes and phylogenetic groups. In addition, ElaD of some branches showed premature translation termination.ConclusionThe widespread occurrence of the elaD gene among various E. coli strains suggests its potential significance in E. coli, although its precise functional role remains to be elucidated.